Seismic stratigraphy and subsidence analysis of the southern Brazilian margin (Campos, Santos and Pelotas basins) - Contreras, Jorham; Zühlke, Rainer; Bowman, Scott; Bechstädt, Thilo (Marine and petroleum geology, 2010)
The Campos, Santos and Pelotas basins have been investigated in terms of 2D seismo-stratigraphy and subsidence. The processes controlling accommodation space (e.g. eustacy, subsidence, sediment input) and the evolution of the three basins are discussed. Depositional seismic sequences in the syn-rift Barremian to the drift Holocene basin fill have been identified. In addition, the subsidence/uplift history has been numerically modeled including (i) sediment flux, (ii) sedimentary basin framework, (iii) relation to plate-tectonic reconfigurations, and (iv) mechanism of crustal extension. Although the initial rift development of the three basins is very similar, basin architecture, sedimentary infill and distribution differ considerably during the syn-rift sag to the drift basin stages. After widespread late Aptian-early Albian salt and carbonate deposition, shelf retrogradation dominated in the Campos Basin, whereas shelf progradation occurred in the Santos Basin. In the Tertiary, these basin fill styles were reversed: since the Paleogene, shelf progradation in the Campos Basin contrasts with overall retrogradation in the Santos Basin. In contrast, long-term Cretaceous-Paleogene shelf retrogradation and intense Neogene progradation characterize the Pelotas Basin. Its specific basin fill and architecture mainly resulted from the absence of salt deposition and deformation. These temporally and spatially varying successions were controlled by specific long-term subsidence/uplift trends. Onshore and offshore tectonism in the Campos and Santos basins affected the sediment flux history, distribution of the main depocenters and occurrence of hydrocarbon stratigraphic-structural traps. This is highlighted by the exhumation and erosion of the Serra do Mar, Serra da Mantiqueira and Ponta Grossa Arch in the hinterland, as well as salt tectonics in the offshore domain. The Pelotas Basin was less affected by changes in structural regimes until the Eocene, when the Andean orogeny caused uplift of the source areas. Flexural loading largely controlled its development and potential hydrocarbon traps are mainly stratigraphic.
Gesehen am 07.06.2023